Vol. 3, No. 1, September 2021 - Khairul Anwarudin (Scientia Regendi, 2021)
Network security is important in The University of Muhammadiyah Cirebon Server. The purpose of this study (1) to determine the impact of vulnerabilities on local networks, (2) to know the implementation of security in the form of NIDN, NIPS, Snort, suricata and Pfsense to maintain data confidentiality, data authenticity and data availability. OWASP Top 10 method with data collection Prepare, Plan, Design, Implementation, Operation, Optimization. The results of the study showed that vurnerability assessment has different values from difficult level with a value of 1 to easy with a value of 3 in network attacks through OWASP Top 10, as well as with the implementation of NIDS, NIPS in Snort, suricata and Pfsense can detect and provide protection, defense from DdoS attackers, Sniffing Attack and Scanner Attack on lan network of Muhammadiyah University of Cirebon. In conclusion, in the implementation of NIDS, NIPS Snort, Suricata and PfSense is very effective in restraining and resisting attackers in the network of Muhammadiyah University of Cirebon.